Analisis Framing Pemberitaan Pariwisata Kal-Tim Pada Media Online Detik.Com dan Tribunkaltim.Co - Nurhaliza, Jihan; Agustian, Jaka Farih; WS, Johantan Alfando WS; Juwita, Rina (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
The purpose of this research is to analyze the framing of Kal-Tim tourism news on online media Detik.Com and Tribunkaltim.Co. This research method is qualitative. This research uses the framing analysis model of Zhongdang Pan and Gerald M. Kosicki.   The data sources used are secondary data sources. The data collection techniques used in this research are through documentation and observation (observation). The results of this study are that the framing of tourism news in East Kalimantan by online media Detik.com and TribunKaltim.co, shows that both consistently adopt the framing of sustainable development and economic improvement of local communities. Detik.com, through its news stories that include titles such as "Don't Expect Disneyland-like Tourism in IKN" and "Tourism Concept in the Archipelago's Capital City Will Be 'Green-green,'" emphasizes aspects of environmental preservation and sustainable development. In line with that, TribunKaltim.co also strengthens the framing of sustainable development with a focus on ecotourism and environmental preservation. Both media actively provide support for the development of the Indonesia Nusantara Special Economic Zone (KEK) in East Kalimantan, creating a positive narrative regarding the economic potential and environmental preservation that can be generated through the development of the tourism sector.